Relationship Between Dietary Omega-3 and Omega-6 Polyunsaturated Fatty Acids Level and Sarcopenia. A Meta-Analysis of Observational Studies - Zhang, Yi; Guo, Hongbin; Liang, Jieyu; Xiao, Wenfeng; Li, Yusheng (Frontiers in Nutrition, 2022)
Objective: This study investigates the relationship between dietary omega-3 and omega-6 polyunsaturated fatty acids (PUFAs) levels and sarcopenia. Methods: A comprehensive literature search in the databases of PubMed, Web of Science, and Embase (up to July 2021) were conducted to identify the observational studies on the relationship between dietary omega-3 and omega-6 PUFAs level and sarcopenia. The pooled odds ratio (OR) of sarcopenia for the highest vs. lowest dietary omega-3 and omega-6 PUFAs level and the standard mean difference (SMD) of dietary omega-3 and omega-6 PUFAs levels for sarcopenia vs. control subjects were calculated. Results: A total of six studies were identified in this meta-analysis. The overall multi-variable adjusted OR showed that dietary omega-3 PUFAs level was inversely associated with sarcopenia (OR = 0.41, 95% CI: 0.26–0.65; P = 0.0001). Moreover, the overall combined SMD showed that the dietary omega-3 PUFAs level in sarcopenia was lower than that in control subjects (SMD = −0.19, 95% CI: −0.32 to −0.07; P = 0.002). With regard to dietary omega-6 PUFAs level, the overall multi-variable adjusted OR suggested no significant relationship between dietary omega-6 PUFAs level and sarcopenia (OR = 0.64, 95% CI: 0.33–1.24; P = 0.19). However, the overall combined SMD showed that the dietary omega-6 PUFAs level in sarcopenia was slightly lower than that in control subjects (SMD = −0.15, 95% CI: −0.27 to −0.02; P = 0.02). Conclusion: Our results suggested that the dietary omega-3 PUFAs level was inversely associated with sarcopenia. However, current evidence is still insufficient to demonstrate the definite relationship between dietary omega-6 PUFAs levels and sarcopenia. More well-designed prospective cohort studies with the dietary omega-3/omega-6 PUFAs ratio are still needed.